Reconstruction of midface defects after surgical treatment of skull base tumors - I. Yu. Belov; N. A. Primak; N. K. Samochernykh; K. A. Chizhova; I. A. Kurnosov; S. Ya. Chebotarev; D. A. Gulyaev (Опухоли головы и шеи)
Aim. To perform a retrospective analysis of the results of surgical treatment of patients with anatomically widespread malignant skull base tumors and evaluate the possibility of using various types of closure of skull base defects.   Materials and methods. The study is based on a retrospective analysis of medical records of 139 patients with midface tumors aged 14 to 77 years, operated from 1995 to 2023. Histological structure of the tumors was different. we divided all methods of reconstruction of midface defects into two groups. In the group 1, plastic closure of the defect was per-formed using flaps from anatomical areas located close to the defect. In the group 2, reconstruction was performed using flaps from distant anatomical areas.   Results. In the postoperative period, we did not observe gross cicatricial face deformities, impaired chewing and swallowing functions due to cicatricial contractures of chewing muscles. Titanium mesh for reconstruction was used in 68 (48.9 %) cases. The osteoperiosteal aponeurotic flap was used in 5 cases, of which in 3 (3.8 % of the total number of patients of the 1st group) – in combination with the temporal muscle. The thoracodorsal flap was used in 62 (44.6 %) patients. various methods of its movement and combination with the anterior dentate muscle were used. In 41 (66.1 %) cases, good cosmetic and functional results were obtained. These indicators correlated with adequate choice of reconstruction method allowing elimination of most of the impaired functions.   Conclusion. The use of the presented technologies for plastic closure of post-resection defects of various parts of the skull base, including those combined with extensive damage to the midface, leads to leveling of the cosmetic and functional consequences of surgical aggression.